2023
DOI: 10.1038/s41420-023-01634-4
|View full text |Cite
|
Sign up to set email alerts
|

FNDC5 inhibits autophagy of bone marrow mesenchymal stem cells and promotes their survival after transplantation by downregulating Sp1

Huan Wei,
Shuaiye Liu,
Tingting Wang
et al.

Abstract: Regenerative therapy based on mesenchymal stem cells (MSCs) has great promise to achieve functional recovery in cerebral infarction patients. However, the survival rate of transplanted MSCs is extremely low because of destructive autophagy caused by the harsh ischemic microenvironment in cerebral infarct tissue. The mechanism by which fibronectin type III domain protein 5 (FNDC5) regulates autophagy of transplanted bone marrow-MSCs (BMSCs) following ischemic injury needs to be elucidated. In this study, we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…However, the detailed mechanism of miR-150-5p on the osteogenic differentiation of BMSCs has not been further studied by Geng Y, et al, but miR-150-5p has been found to inhibit the osteogenic differentiation of ankylosing spondylitis fibroblasts [ 14 ] and adipose-derived stem cells [ 15 ]. At the same time, it is well known that the protein encoded by the FNDC5 gene (iris) has been found to regulate the differentiation of BMSCs [ 16 , 17 ], including promoting the osteogenic differentiation of BMSCs [ 18 ]. Therefore, miR-150-5p may be involved in the regulation of osteogenic differentiation of BMSCs by regulating the expression of FNDC5.…”
Section: Introductionmentioning
confidence: 99%
“…However, the detailed mechanism of miR-150-5p on the osteogenic differentiation of BMSCs has not been further studied by Geng Y, et al, but miR-150-5p has been found to inhibit the osteogenic differentiation of ankylosing spondylitis fibroblasts [ 14 ] and adipose-derived stem cells [ 15 ]. At the same time, it is well known that the protein encoded by the FNDC5 gene (iris) has been found to regulate the differentiation of BMSCs [ 16 , 17 ], including promoting the osteogenic differentiation of BMSCs [ 18 ]. Therefore, miR-150-5p may be involved in the regulation of osteogenic differentiation of BMSCs by regulating the expression of FNDC5.…”
Section: Introductionmentioning
confidence: 99%